Supporting Elementary Students' Sourcing of Historical Texts. (24th April 2018) - Popp, Jacquelynn S.; Hoard, Jodi
Abstract: Sourcing involves interrogating historical documents, asking questions about their attributes to determine their relation to the historical event or time period under study. In this article, a university researcher and a sixth‐grade teacher describe a set of heuristics that the teacher developed for supporting her students' sourcing of historical texts. The heuristics derive from findings of a longitudinal case study that the researcher conducted about the teacher's learning to shift to a disciplinary literacy approach in her social studies classroom, as well as the teacher's insights about her own process of learning to scaffold her students' sourcing. Considering the limited resources for addressing elementary teachers' sourcing instruction, these heuristics are offered so other teachers can adopt and adapt them to their own teaching contexts to meet the specific, diverse needs of their students.